Termination Of Employment Due To the Global Manufacturing Crisis: A Comparative Study of Worker Protection in Indonesia, Germany, and Vietnam - Lalu Hadi Adha; Yazid Fathoni; Diangsa Wagian (Lembaga Bale Literasi, 2026)
This study aims to analyze the driving factors of the global manufacturing crisis and evaluate the legal protection frameworks for workers facing mass layoffs in Indonesia, Germany, and Vietnam. It explores how each nation adapts its national regulations to mitigate the socio-economic impacts of geopolitical instability and the global economic slowdown. Using a juridical-normative method with a comparative approach, the analysis is conducted through a legal-dogmatic lens, processing materials through technical, teleological, and external systematization levels.The study finds that although the manufacturing crisis is a shared global phenomenon, protective responses vary significantly. Indonesia relies on the Job Creation Law and the Job Loss Guarantee (JKP) social safety net. Germany emphasizes